A MOF-derived coral-like NiSe@NC nanohybrid: an efficient electrocatalyst for the hydrogen evolution reaction at all pH values. Issue 48 (16th October 2018) - Huang, Zhaodi; Liu, Jianhua; Xiao, Zhenyu; Fu, Hui; Fan, Weidong; Xu, Ben; Dong, Bin; Liu, Di; Dai, Fangna; Sun, Daofeng
Abstract : A coral-like NiSe@NC nanohybrid derived from Ni-MOFs has been synthesized. The performance of the complex in the hydrogen evolution reaction at all pH values was studied. Abstract : A coral-like NiSe@NC nanohybrid as an effective electrocatalyst for the hydrogen evolution reaction (HER) at all pH values, constructed via the in situ selenation of a Ni-MOFs precursor, is reported. The electrocatalyst shows overpotentials of 123 mV, 250 mV and 300 mV in 0.5 M H2 SO4, 1.0 M KOH and 1.0 M PBS, respectively, to afford a current density of 10 mA cm −2 . Meanwhile, NiSe@NC also exhibits a small Tafel slope and superior long-term stability over a wide pH range. The excellent electrocatalytic performance should be ascribed to the unique coral-like structure with a large BET specific surface area (125.4 m 2 g −1 ) and mesoporous features, as well as synergistic effects between NiSe nanocrystals and highly conductive N-doped porous carbon.